Towards accounting harmonization in Europe: a multinational survey among budget experts. (June 2022) - Frintrup, Markus; Schmidthuber, Lisa; Hilgers, Dennis
Severe fiscal problems, the insufficient comparability of financial information and increasing demands for better accountability require national governments and international organizations to change their current accounting regimes and to move towards a system of standardized accounting practices. As the International Public Sector Accounting Standards have insufficiently moved Europe towards accounting harmonization in recent years, the European Commission currently aims to suggest the adoption of European Public Sector Accounting Standards. Based on a multinational survey among budget experts, the current article investigates budget experts' perceptions towards adopting the European Public Sector Accounting Standards. The findings compare attitudes towards new accounting practices and European Public Sector Accounting Standards reform expectations on a comparative basis, and relate them to the current national accounting system and contextual factors. Empirical results indicate great variation in terms of European Public Sector Accounting Standards reform expectations across countries. The study concludes with discussing the implications of the findings for international accounting research, accounting harmonization and the development of a European accounting system. Points for practitioners: In this early stage of European Public Sector Accounting Standards development, understanding the factors associated with a country's decision to adopt them could be helpful for practitioners and professionals. The current study identifies information technology costs as a potential barrier to implementing the European Public Sector Accounting Standards. Politicians and standard setters might take this into account while developing the European Public Sector Accounting Standards. Furthermore, this article reveals that encouraging the voluntary introduction of accrual accounting in the first stage of European Public Sector Accounting Standards development might be the appropriate approach of the European Commission.